Pengaruh Model Pembelajaran Problem Based Learning terhadap Kemampuan Berpikir Ilmiah Peserta Didik - Ulfita Sari; Salim Salim; Safran Hasibuan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to determine the effect of problem based learning model on students' scientific thinking skills. This type of research is experimental research, the design used is a quasi-experimental with a pretest posttest non-equivalent control group design. This research was conducted in class IV at one of the Private Elementary Madrasahs in Batubara Regency. The population of the study was all students in class IV with a total sample of 30 students. The instrument used was a scientific thinking ability test in the form of 5 essay questions. The results of this study used the analysis prerequisite test, namely the normality test and the homogeneity test. The hypothesis test in this study used the paired sample t test statistic on the IBM SPSS version 29 program, the sig value was obtained. (2tailed) is 0.001 <0.05 so that Ho is rejected and Ha is accepted indicating the influence of the problem based learning model on students' scientific thinking skills. For further researchers, this research should be completed by examining other aspects in detail that have not been reached at this time.